1998
DOI: 10.1017/s0014479798004049
|View full text |Cite
|
Sign up to set email alerts
|

Farmer Acceptability Criteria in Breeding Cowpea

Abstract: Cowpea (Vigna unguiculata) farmers from diverse geographical areas in northern Cameroon selected breeding lines from on-station trials for their own ®elds and explained their reasons (criteria) for making the selections. The average selection intensity employed by farmers varied from 6 to 17% and was similar to that employed by plant breeders. Their selection criteria fell into three broad categories relating to yield, preference and quality, and labour, which were very consistent over years, locations and gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
53
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(61 citation statements)
references
References 5 publications
8
53
0
Order By: Relevance
“…When asked whether or not soil fertility improvement should be added to the list of criteria, the farmers responded negatively. Our findings confirm the conclusions of Kitch et al (1998) who reported that in Cameroon farmers' acceptance criteria and preferences for cowpea varieties were strongly influenced by market preferences.…”
Section: Economic Analyses and Farmers' Evaluation Of The Cowpea Varisupporting
confidence: 91%
“…When asked whether or not soil fertility improvement should be added to the list of criteria, the farmers responded negatively. Our findings confirm the conclusions of Kitch et al (1998) who reported that in Cameroon farmers' acceptance criteria and preferences for cowpea varieties were strongly influenced by market preferences.…”
Section: Economic Analyses and Farmers' Evaluation Of The Cowpea Varisupporting
confidence: 91%
“…Participatory research has demonstrably improved the cultivar selection process [21,22]. In contrast, soil fertility methods are harder to disseminate because of the requirements of land, labor, and cash resources, with few successful models to follow [23].…”
Section: Introductionmentioning
confidence: 99%
“…Two such trap crops against S. hermonthica are cotton (Sauerborn et al 2000) and cowpea (Gbèhounou and Adango 2003). Cotton and cowpea are also important (cash) crops in savannah regions of Africa (Kitch et al 1998), including north Cameroon. Cowpea, however, is susceptible to another species of Striga: Striga gesnerioides (Dubé and Olivier 2001).…”
Section: Introductionmentioning
confidence: 99%